BOOK REVIEW OFFLIPPED BY WENDELIN VAN DRAANEN - Puspitasari, Anita Ratna (LANTERN (Journal on English Language, Culture and Literature), 2015)
Literary work exists because of someone who expresses thoughts and brilliant ideas that are easy to understand and got someone interested. Literary work is dealing with human life. Literature and humans are close relationship, because of its association with aspects of human of life which gave people to use their imagination like a story. Mursal Esten (1978:4) says “Literature or literature is disclosure of the facts as its artistic and imaginative manifestation of human life (and society) through language as medium and has positive effect of human life”. Flipped is a novel that tells love written by Wendelin Van Draanen. Flipped is one of the great works of Wendelin. She has a positive comment about this novel. Flipped is published in New York 2001 and has been repeatedly printed. Flipped had been filmed and it became favorite film for various groups of people, because the story is interesting and is also added in the comedy scene.